Impact of Ethanol on the Evolution of One-Step Synthesized Gold Nanoplates and Nanostars and Their Effects on Raman Signal Enhancement - Fania, Ananda; Sambudi, Nonni Soraya; Putri, Kirana Yuniati; Herbani, Yuliati; Hidayah, Affi Nur (UI Scholars Hub, 2025)
Gold nanoplates and nanostars were synthesized from a gold metal salt solution (HAuCl4) using a one-step synthesis method of ultraviolet C (UVC) light irradiation. The gold salt solution was mixed with ethanol in 6 mL with the following ratios: (1.5:4.5, 3:3, and 4.5:1.5), and subsequently irradiated with UVC light. Changes in localized surface plasmon resonance (LSPR) shifts were observed in real time at 30-min intervals for 2 h. The synthesis process produces gold nanoplates. While gold nanostars were synthesized from a solution of gold salt combined with ethanol, ascorbic acid, and AgNO3, maintaining a consistent ratio of ion solution to ethanol similar to that of nanoplates and mixed with 50 μL of ascorbic acid and different concentrations of AgNO3 (10 μL, 50 μL, and 100 μL), followed by UVC light irradiation. Changes in LSPR were also monitored in real time every 30 min for 2 h. The findings indicated that the optimal synthesis of gold nanoplates and nanostars occurred at a 3 mL:3 mL ratio of ion solution to ethanol, with the addition of 100 μL of AgNO3 for nanostars, as evidenced by the results of TEM characterization. Subsequently, gold nanoplates and nanostars were deposited onto silicon wafers with a volume of 1 mL and dried on a hot plate. They were then dropped with the paraquat pesticide analyte and analyzed using portable Raman spectroscopy at a wavelength of 785 nm. This result demonstrates that gold nanostars enhanced the Raman signal more significantly than gold nanoplates. This study is beneficial for creating an efficient and rapid detection method for the pesticide paraquat, which remains prevalent in Indonesia despite being prohibited in other nations. The quality of nanoparticles, such as gold nanostars, which have strong plasmonic properties and can enhance the sensitivity of the Raman signal, significantly affects the detection of analytes using surface enhanced Raman spectroscopy, thereby facilitating an easier and rapid detection process for paraquat pesticides